Legitimising liberal militarism: politics, law and war in the Arms Trade Treaty. Issue 5 (3rd May 2016) - Stavrianakis, Anna
Abstract: Post-cold war efforts to knit together human rights and international humanitarian law in pursuit of tougher arms transfer control reached their apogee in the UN Arms Trade Treaty (ATT). In contrast to dominant accounts based on human security norms, I argue that a key effect of the ATT is to legitimise liberal forms of militarism. During negotiations the US and UK governments justified their arms export practices in terms of morality, responsibility and legitimacy. More broadly their arms transfer practices are explained away by reference to national regulatory regimes that exceed the standards set out in the ATT. Arms transfers to Egypt and intra-Western transfers illustrate the way these justifications and regimes serve to shield US–UK weapons transfers and use from scrutiny and accountability. Rather than signalling the victory of human security, the ATT is better understood as facilitating the mobilisation of legitimacy for contemporary liberal forms of war fighting and war preparation.